The history and meaning of the "other" Lekha Dodi poem(s) - Kaunfer, Elie G. (2008)
Shlomo Alkabetz's poem Lekha dodi is one of the most famous works of kabbalistic poetry. Yet Alkabetz's poem may not be the original version of Lekha dodi. An oftignored poem (poems?) containing the same refrain, and two near-identical verses, was published by Moshe ibn Machir, leader of a community in nearby Ein Zeitim, in סדר היום. In this paper, we analyze the history of this version of Lekha dodi and its relationship to that of Alkabetz, concluding that this version of Lekha dodi most likely predated Alkabetz's. It is a work with clear themes: the redemption of the past hinting at the redemption of the future, and veiled references toward messianism, in addition to numerous references to kabbalistic understanding. The Lekha dodi poem(s) of סדר היום shed further light on the mystical, national, and messianic understanding of Shabbat in sixteenth-century Safed.
Keywords: Jüdische Literatur